An Overview of Registered Clinical Trials on Glucosinolates and Human Health: The Current Situation - Marino, Mirko; Martini, Daniela; Venturi, Samuele; Tucci, Massimiliano; Porrini, Marisa; Riso, Patrizia; Del Bo', Cristian (Frontiers in Nutrition, 2021)
Epidemiological studies suggest a potential role of glucosinolates (GSLs) and isothiocyanates on human health. However, evidence from intervention studies is still insufficient, also due to heterogeneity in features of study design, duration, participants, food/components administered and outcomes analyzed. The current review aims to provide an overview of the trials on GSLs and GSL-rich foods registered over the last 20 years, with the intention to summarize the main topics and results, but also the existing gaps that still need to be covered. Studies were collected by using ClinicalTrials.gov and International Standard Randomized Controlled Trial Number (ISRCTN) registry. A total of 87 registered trials were identified; most of them were performed by using extracts or pure compounds (n=60) while few were conducted with GSL-rich foods (n=27). In detail, sulforaphane was the most investigated compound, while broccoli the most frequent food tested in the trials. The majority of the studies assessed the health effects of GSLs focusing on outcomes related to cancer and cognitive function, even if the current findings are not univocal. Emerging topics included also the study of GSLs and gut microbiota interaction and impact on skin health. Further attention was also drawn to the bioavailability of GSLs and/or derivatives from foods, extracts and single compounds by also considering the contribution of the different genetic polymorphisms. In conclusion, although considerable efforts have been made to study GSLs and GSL-rich foods, further studies are necessary to provide evidence-based research and corroborate the findings obtained. The interindividual response due to genetic polymorphisms should be further investigated in order to explore the contribution on the overall beneficial effect.